Valgus extension overload: Diagnosis and treatment - Dugas, J. R. (Clinics in Sports Medicine, 2010)
Valgus extension overload (VEO) is a constellation of symptoms and pathology commonly seen in the overhead athlete. Athletes in many sports may experience VEO and other common pathologies related to the high repetitive stresses generated by the overhead throwing motion. VEO is characterized by reproducible pain that is elicited by repeatedly forcing the elbow into terminal extension while applying a valgus stress to the elbow. Pain at the posteromedial tip of the olecranon process is pathognomonic of the condition. Olecranon stress fractures are rare, but can cause significant discomfort and, if unrecognized or untreated, can lead to significant pain and dysfunction. Both of these conditions are treated initially with rest from throwing, followed by gradual return to throwing through an interval throwing program. When conservative measures fail, minimally invasive or arthroscopic surgical procedures can be used to address the problem. Successful return to competitive overhead sports is expected at all levels of competition with these conditions.